Temperature representation in the Drosophila brain - Frank, Dominic D. (Nature, 2015)
In Drosophila, rapid temperature changes are detected at the periphery by dedicated receptors forming a simple sensory map for hot and cold in the brain(1). However, flies show a host of complex innate and learned responses to temperature, indicating that they are able to extract a range of information from this simple input. Here, we define the anatomical and physiological repertoire for temperature representation in the Drosophila brain. First, we use a photolabeling strategy(2) to trace the connections that relay peripheral thermosensory information to higher brain centers, and show that they largely converge onto three target regions: the Mushroom Body, Lateral Horn (well-known centers for sensory processing) and the Posterior Lateral Protocerebrum, a region we now define as a major site of thermosensory representation. Then, using in vivo calcium imaging(3), we describe the thermosensory projection neurons selectively activated by hot or cold stimuli. Fast-adapting neurons display transient “ON” and “OFF” responses and track rapid temperature shifts remarkably well, while slow-adapting cell responses better reflect the magnitude of simple thermal changes. Unexpectedly, we also find a population of ‘broadly-tuned’ cells that respond to both heating and cooling, and show that they are required for normal behavioral avoidance of both hot and cold in a simple 2-choice temperature preference assay. Taken together, our results uncover a coordinated ensemble of neural responses to temperature in the fly brain, demonstrate that a broadly tuned thermal-line contributes to rapid avoidance behavior, and illustrate how stimulus quality, temporal structure, and intensity can be extracted from a simple glomerular map at a single synaptic station.